2 * 10 ^7 / .

( 9.1 * 10 ^-31 , 1.67 * 10^-27 )

:-
2 = 0 , / 1 = ( 1 - 2 / 1 + 2 ) 1

= (9.1 * 10^-31 - 1.67 * 10^-27 / 9.1 * 10^-31 + 1.67 * 10^-27 ) *2 * 10^7
= ( -1.66909 * 10^-27 / 1.67091 * 10^-31 ) *2 * 10^7
/ 1 = - 0.9989 * 2 * 10 ^7 .............. /1 = - 1.9978 * 10^7 /

/1 = ( 2 1 /1 + 2 ) * 2

=( 2 * 9.1 * 10^-31 /9.1 *10^-31 + 1.67 *10^-27 ) *2 * 10^7
= 0.0012 * 2 *10^7

1 = 2.4 * 10^4 /


, 200 . ( , ) . . .
:-
,
+ = ( + ) ( )
+ = 0
= - = .............. = -
= ( 1/2 ^2 + 1/2 ^2 ) - 1/2 ( + ) ^2
200 = 1/2 ^2 + 1/2 ^2 2
400 = ^2 + ^2 ............ = , ^2 = ^2

^2 = ^2 = 200
^2 = 200/ ........ = 200/ ................. = 200/

100 100

3 /








:

=

:

= 0.1 * 9.8 /^2 * 1 = 0.98 . ( )

= 0 / ... ( )

= 0

= 0.98


:

= 0

:

- ( )
- ( )

= 3 /

( - )

= 1/2 * 0.1 * (3 /)^2 = 0.45

:


= +

0.98 + ( ) = + ( - ) = 0 + 0.45 = 0.45

= 0.45 - 0.98 = - 0.53 ( )

:





10

54

162






:

= 54 /


:

= 0
= 162 - 54 = 108 /
= 10 /

= *
108 * 10^3 / 60^2 = 10 *

= 3


.


() = * = ( 54 * 10^3 / 60^2 )*3 = 45

() = 1/2 * * = 1/2 * 10 * 3^2 = 45

= 45 + 45 = 90